Analysis of Domestic Component Level and Company Benefit Weight Calculation in Multi-Story Building Construction Projects: A Case Study of the Pingit Police Dormitory Apartment Project - Bella Ayu Permata Sari; I Nyoman Dita Pahang Putra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The application of the Domestic Component Level (DCL) within the infrastructure construction sector constitutes a strategic policy undertaken by the government to promote the utilization and development of domestic products while reducing reliance on imported goods. In high-rise building projects, the assessment of DCL extends beyond material usage to include the contribution of local services and labor, as reflected in the Unit Price Analysis of work activities. This study is intended to determine the DCL value, the Company Benefit Weight, and the combined Domestic Component Level-Benefit Weight (BMP) value. A quantitative research approach is employed, utilizing secondary data such as the Cost Budget Plan (RAB), Unit Price Analysis (AHS), technical specifications, and unit price lists. The findings indicate that the DCL value reaches 80%, while the BMP value is 3%, resulting in a combined DCL and BMP value of 83% for the Pingit Police Dormitory Apartment construction project. This outcome surpasses the minimum DCL requirement of 25%, indicating that the project is not subject to further evaluation procedures or financial penalties. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production